Pembagian Harta Warisan Secara Kekeluargaan Studi Sosio-Historis Pasal 183 Kompilasi Hukum Islam - Aziz, A. Fauzi (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2022)
The Qur'an's postulate is quite detailed about inheritance and the provisions are final. However, this is inversely proportional to the concept of inheritance that applies to Article 183 of the Compilation of Islamic Law (KHI) which allows the distribution of inheritance by family agreement. From these different concepts, it becomes an attraction to conduct research by focusing the problem on two aspects. First, examine the practice and settlement of the division of inheritance in a familial manner in the lens of jurisprudence. Second, what social factors are behind the division of inheritance with the family system. Judging from the focus of the study, this research is classified as normative legal research. Meanwhile, judging from the data collection operations studied, this research is classified as a literature study. Secondary and primary data were analyzed using analytical descriptive methods using Islamic inheritance theory to analyze KHI data in family inheritance Article 183. Meanwhile, the approach in analyzing data with the statute approach. The results of this study concluded, first, the practice of familial division of heirs was applied after first understanding the share of each of the heirs. This is an absolute requirement for the practice to be allowed. Second, looking at the historical stretch of inheritance from the early days of Islam to the present, there will be a change in law taking into account the customary laws that apply in society and the existence of a career role that applies, especially between men and women.